MAKNA BUNGA SEBAGAI SARANA PERSEMBAHYANGAN UMAT HINDU - Wasudewa Bhattacarya; Ni Wayan Eka Damayanti (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
Flowers are one of the most important means of praying for the Hinduismin Bali. Not only in the western world and in the development of the modernworld, Bali has inherited the tradition of using flowers as a means of prayerfor Hindus, it is even written in the Vedic scriptures. The various colors andtypes of flowers used by Hindus certainly have meanings and are believedto have their own mythology. This research is interesting because flowershave a deep meaning for Hindus. The purpose of this study was to determinethe meaning of flowers in the means of worship of the Hindu community inBali which was analyzed using the theory of Semiotics according to RolandBarthes. To achieve the research objectives, this research uses literaturestudy techniques and observations. This research data analysis method usesdescriptive analysis techniques. The results of this study are (1) the meaningof flowers as a symbol of God and His Manifestations, (2) the meaning offlowers as a symbol of human sincerity, (3) the meaning of flowers as a symbolof grace from God, (4) the meaning of flowers as environmental preservation,and (5) Flowers are good as a means of worship.